A Review of Traditional Methods of Conflict Resolution from a Nigerian-African-Perspective - Fidelis Isomkwo Aboh; Emmanuel Paul Ngele; Emmanuel N Okom; John Augustine Iteh; James Nwachukwu Eze (Borong Newinera Publisher, 2023)
Westernisation and globalization have almost eroded this culture and left in their trail an alien culture of conflict resolution which, in most cases, is at variance with our African ethics and cultural values. The replacement of our grand African methods of conflict resolution with the European methods of conflict resolution has particularly done harm rather than good to our group cohesion as one Nigeria, and generally to our group cohesion as Africans. There is doubtless the fact that an alien culture of conflict resolution on an African soil necessarily undermines our history as one black people, our philosophy as a communal entity and our belief that peace and unity of the collective supersedes the selfish interests of a select few who seek to benefit from conflict. Our history of ethnic clashes, insurgencies and the rise of crime in our African societies attest to the fact that in matters of conflict resolution, Nigerians and indeed Africans have employed the wrong methods, bereft of our African spirit of unity and peace in preference to unrests, upheavals and wars. It is against this backdrop that this paper explored our traditional methods of conflict resolution and made recommendations. In doing this, the paper looked at what conflict is, causes of conflict in Africa, principles of conflict resolution, methods of conflict resolution by the major ethnic nationalities in Nigeria, the use of proverbs rhetoric and folklores in conflict resolution and common methods of conflict resolution in Africa. The paper concluded the discourse with a summary and made some recommendations on the way forward.